Ethanol as a Hydrogenating Agent: Palladium‐Catalyzed Stereoselective Hydrogenation of Ynamides To Give Enamides - Reddy, Alla Siva; Swamy, K. C. Kumara (Angewandte Chemie International Edition, 2017)
Ethanol is shown to act as a hydrogenating agent for ynamides under palladium catalysis. This behavior is different from the normally expected reaction of ethanol addition to alkynes. The reaction shows stereoselectivity for E enamides, which is in contrast to reports using other hydrogenating sources. The method was also extended to ynamines. Alternatively, the use of ethanol and ammonium formate as the hydrogenating source gives Z enamides. The role of ethanol in hydrogenation was demonstrated by means deuterium labeling experiment. One for the road: Ethanol acts as a hydrogenating agent for ynamides under palladium catalysis. This behavior is different from the normally expected addition of ethanol to alkynes. The reactions show stereoselectivity for E enamides, which is in contrast to reports using other hydrogenating sources, and the method was also extended to ynamines. Alternatively, the use of ethanol/ammonium formate as the hydrogenating source gives Z enamides.